Using Chained or Tandem Schedules With Functional Communication Training: A Systematic Review. Issue 1 (January 2023) - Torelli, Jessica N.; Pickren, Sage E.
Chained and tandem schedules are a common method for thinning schedules of reinforcement following functional communication training (FCT) in the treatment of problem behavior. We conducted a systematic literature review and meta-analysis of chained and tandem schedules following FCT to describe treatment characteristics and evaluate effects. We identified 38 articles and found reductions in problem behavior across four measures. Results of a random-effects multilevel meta-analysis of rigorous evaluations showed a significant effect of chained or tandem schedules + FCT on problem behavior relative to baseline. We observed resurgence in 77% of cases and 31% of schedule-thinning transitions. Results showed chained schedules resulted in greater reductions in problem behavior relative to tandem schedules. Exploratory moderator analyses suggested extinction, combined reinforcement, and delay and denial tolerance training procedures were associated with greater reductions in problem behavior relative to other treatment characteristics. Implications for practice and future research are discussed.